2017
DOI: 10.3349/ymj.2017.58.1.123
|View full text |Cite
|
Sign up to set email alerts
|

Lenticulostriate Artery Involvement is Predictive of Poor Outcomes in Superficial Middle Cerebral Artery Territory Infarction

Abstract: PurposePatients with superficial middle cerebral artery (MCA) territory infarction may have concomitant lenticulostriate artery (LSA) territory infarction. We investigated the mechanisms thereof and the outcomes of patients with superficial MCA territory infarction according to the presence or absence of LSA involvement.Materials and MethodsConsecutive patients with first-ever infarction in the unilateral superficial MCA territory were included in this study. They were divided into the superficial MCA only (SM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…the leptomeningeal branches, of the parent artery, occlusion of a latter branch may lead to occurrence of both a superficial and a deep ischemic lesion. The association of those two types of infarcts was described by some other authors as well, although most often as a consequence of the global cerebral or systemic atherosclerosis [37].…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…the leptomeningeal branches, of the parent artery, occlusion of a latter branch may lead to occurrence of both a superficial and a deep ischemic lesion. The association of those two types of infarcts was described by some other authors as well, although most often as a consequence of the global cerebral or systemic atherosclerosis [37].…”
Section: Discussionmentioning
confidence: 66%
“…The pathologic changes were noticed in patients with a visible atherosclerosis of the large arteries at the base of the brain, but in none within the control group. Similarly, some authors found a correlation between general atherosclerosis and the appearance of cerebral infarcts [37,39]. This may have three explanations.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In a MRA, the internal carotid artery and vertebral artery system are often normal. MR fiber tracking was helpful, which demonstrated that the severity of motor deficit depends on the extent of the infarct in the upper part of the internal capsule (45,46).…”
Section: Radiological Featuresmentioning
confidence: 99%
“…Stroke is a major contributing factor for brain ischemia and the third leading cause of mortality in Western countries. Brain ischemia leads to movement, visual, sensory, and behavioral disorders, especially aphasia and impaired spatial learning [24].…”
Section: Introductionmentioning
confidence: 99%